A STUDY OF ENVIRONMENTAL APPROACH IN EARLY DESIGN STAGE - Indarti, Fenty Ratna (Border: Jurnal Arsitektur, 2020)
Due to the ozone layer depletion, global warming and climate change, there is a significant increase to reduce carbon emission. Practitioners and academia undertake studies to promote environmentally friendly built environments. Developed countries have established specific standards to achieve a carbon neutral as their commitment to contribute for a better earth condition. Design phases are considered as the early stage where the environmental approach needs to be applied to predict the building performance as soon as possible to maximise the energy efficiency of the proposed building. Another significant factor affecting the building energy performance is climate. Climate becomes the first parameter to generate building proposals as it is contextual to the site. This study aims to assess the application of environmental approach in designing educational building in temperate climate in the early design stage. The combination of design and simulation helps to define the best design proposal to adopt passive design that harvest the environment condition as much as possible to deliver comfort into the building.